ANALISIS TARIKAN PERJALANAN DI JEMBATAN MAHAKAM SIMPUL RUAS JALAN SLAMET RIYADI – JALAN UNTUNG SUROPATI KOTA SAMARINDA - Abdul Malik (KURVA MAHASISWA, 2016)
Causes Bridge area of land use changes in the function which later cause problems,community activities for the activity causing seizures-trip generation that can overload network pathsroad to centers of activity.The problems that occurred in the area of Samarinda Mahakam bridge, has a formulation ofthe problem as follows: 1. How to pull model mahakam bridge trip. 2. How to test results R to pullmahakam bridge. 3. How to test results F to pull mahakam bridge.For data corresponding to the problem under study, the researchers used data collectiontechniques spread of 350 sheets questionnaire and by interviewing family or the way done with theintent to obtain direct information about the list of questions on the questionnaire sheet and SPSS 20software program that is used to perform calculations.From the data traffic growth samarinda mahakam bridge, known of vehicles number is 2925vehicles. Results of data obtained from the questionnaire contained 3 Modeling traction drive is theearnings in a month (X5), last education (X3), and mean a trip across the bridge mahakam (X6). Sothat the dependent variable that is formed is Y (means of transport used). Of the three models have incommon regrensi Y = 0,843 + 0,307 (X5) + 0,102 (X3) + 0,173 (X6) and Value Test R (Coefficient ofCorrelation multiple = 0,560 Showing the level of the relationship of the dependent variable(dependent variable) with independent variables (Variables ) at a rate of Strong Correlation showedthat 56% of (the dependent variable) can be explained by perunahan in the variable (X5) earnings in amonth, (X3) last education and (X6) mean a trip across the bridge mahakam, (dependent variable).